Crimes and Disputes : Missed Opportunities and Insights from a National Data Collection Effort in Papua New Guinea - Akmeemana, Sakuntala (World Bank, Washington, DC, 2014)
As in many developing countries, data collection has proved to be a considerable challenge in Papua New Guinea (PNG). A welcome effort at data collection on dispute incidence and personal security was made in PNG's household income and expenditure survey (HIES or the Survey), (2009-2010) an experience that also highlights some of the challenges of such an exercise. For the first time, the HIES asked questions about dispute incidence and personal security. The survey was administered in all provinces of PNG to a nationally and regionally representative sample of over 4,000 households, and provides comprehensive data about the socio-economic status of households. The results are representative at the level of the country's four regions (Southern, Highlands, Momase, and Islands) plus the metropolitan area (which comprises the major urban areas of National Capital District and Lae), as well as for a rural or urban breakdown within each region. This briefing note highlights some of the main findings on dispute and personal security, noting which results need to be treated with caution. It also distils a number of lessons from this data collection effort.